Social Entrepreneurship in the Colombian Choco: An investigation into the processes , obstacles and Impacts of the Commercialization of Smoked Fish - Stacy, Tyler (Department of Sociology, 2014)
This study looks at the commercialization of smoked fish on the Pacific coast of Colombia. Innovative individuals have identified this historical process of fish preservation as a social development tool, and through this are attempt-ing to alleviate prevailing local social problems. These processes, however, do face certain obstacles, and the impacts of these processes are felt in various lay-ers. Through fieldwork carried out in 2009, a qualitative investigation was car-ried out in three certain areas: Impacts of the establishment of smoked fish op-erations; obstacles to production and sustainable commerce; and future goals in the commercialization of smoked fish. This study will show the impacts in the form of provision of employment, wealth creation, and the effects on relation-ships. I will move on to highlight the obstacles they face in access to fish, capital, infrastructure, industrial fishing, arrival of floating cocaine, and market trends. The study caps off with the emergence of future goals in the acquisition of a mo-torboat, increased capital, improved production and business processes, and enhanced group dynamics. This investigation serves as a platform into the explo-ration of social entrepreneurship operations in the Colombian Choco, specifically those of smoked fish commercialization, and how we can better understand these obstacles and the future needs practitioners and local citizens are facing.